Molecular Basis of the Differentiation and Function of Virus Specific Follicular Helper CD4+ T Cells - Huang, Qizhao; Hu, Jianjun; Tang, Jianfang; Xu, Lifan; Ye, Lilin (Frontiers in Immunology, 2019)
Follicular helper T cells are key components of the CD4+ T cell-mediated immune response during viral infection, helping virus-specific B cells to differentiate into plasma cells that produce high-affinity virus-neutralizing antibodies. Similar to Tfh cells generated in other conditions, the differentiation of virus-specific Tfh cells can also be characterized as a process involved multiple factors and stages, however, this process also exhibits distinct features. Here, we mainly focus on the current understanding of Tfh fate commitment, functional maturation, lineage maintenance and memory transition and formation in the context of viral infection.